Detecting Delirium in Older People: The Development of a New Web-Based Tool for Family Caregivers - Hou, Jia; Wongpakaran, Nahathai; Wongpakaran, Tinakon; Tamdee, Decha; Rattakorn , Phuanjai; TSOH , Joshua (Biomedical Sciences and Clinical Medicine, 2025)
Objective Delirium is a common yet under-recognized neuropsychiatric condition in older adults. In Thailand, many family caregivers lack accessible tools that can help them identify this condition at home. This study aimed to develop and evaluate a bilingual, web-based tool, “delirium-detect,” to support early delirium detection by non-professional caregivers. Methods This research and development study involved literature reviews, expert interviews, key informant input, and focus group discussions to design a 22-item symptom checklist available in both Thai and English and in desktop and mobile formats. A pretest (n = 17) and a pilot test (n = 11) were conducted with family caregivers of hospitalized older adults diagnosed with delirium. Tool feasibility and user satisfaction were as-sessed using descriptive analysis. Results Expert reviews confirmed strong content validity (CVI = 1.00). All pilot participants met DSM-5 criteria for delirium using the tool, supporting its criterion validity. The average time to complete the questionnaire was 9.09 minutes. User feedback indicated high satisfaction: 54.5% “liked” and 18.2% “strongly liked” the tool, while 72.8% found it easy or extremely easy to use. Conclusions The “delirium-detect” tool demonstrated preliminary validity, practicality, and user-friendliness, supporting its potential for early delirium detection by family caregivers. Further validation in larger and more diverse populations is recommended to enhance generalizability.